Ida ao inferno verde:experiências da migração de trabalhadores do Ceará para a Amazonia (1942/1945) - Barboza, Edson Holanda Lima (2005)
Amazon lost the rubber monopoly at the deginning os the twentieth century because of the rational production by Enghish companies in the Far East promoting a price fall of this product in the international market The trade and suppying system of rubber-trees broke down reflected in the decrease of the populational rate registered by researches in 1920 and 1940. During the Second World Wwar the arrangement of Brazilian government to the ally block caused the signature of a serie of agreements with American government “Washington Agreements” Brazil assumed compromisse to sell to the United States its overplus production of rubber and execute a plan of revitalization to Amazon ground with the intention to increase the exploration of native rubber-trees In exchanging it would receive investments to modernize the army and build a siderurgic company This way the “Rubber Battle” began in 1942 - campaigns that stimulated the bringing in of rubber materials used for recycling and the migratory waves to Amazon We discuss the reasans that the State of Ceara has been the main pole of recruitment of migrant workers who received the nomination of “ rubber soldiers” The systematic advertisements and the creation of specialized services to organize the migration don’t explain the questions themselves We consider also the actions of controlling over the inlander populations that faced the drought in 1942 and the tradition of migration from Ceara to Amazon supported by webs of relationship and aggregated people stabilished since the end of the nineteenth and that weren’t broken completely with rubber decadence Contradictorily the internal migration polics founded by the New State resulted in the degradation of many families Our dissertation searches for understanding the implantation and execution of recruting in Ceara privileging documents that permitted to make a profile of mobilized workers and their expectations